Isolation and Identification of Fungal Strains from Lake Soil in and Around Ranipet Area Vellore District - A Paneerselvam, Dr (International Journal of Pharmaceutical & Biological Archive, 2013)
Isolation and Identification of Fungal Strains from Lake Soil in and Around Ranipet Area Vellore District